Connective tissue growth factor and integrin αvβ6: A new pair of regulators critical for ductular reaction and biliary fibrosis in mice. Issue 2 (February 2015) - Pi, Liya; Robinson, Paulette M.; Jorgensen, Marda; Oh, Seh‐Hoon; Brown, Alicia R.; Weinreb, Paul H.; Trinh, Thu Le; Yianni, Protopapadakis; Liu, Chen; Leask, Andrew; Violette, Shelia M.; Scott, Edward W.; et al.
<x xml:space="preserve">Abstract</x> Connective tissue growth factor (CTGF) is a matricellular protein that mediates cell‐matrix interaction through various subtypes of integrin receptors. This study investigated the role of CTGF and integrin αvβ6 in hepatic progenitor/oval cell activation, which often occurs in the form of ductular reactions (DRs) when hepatocyte proliferation is inhibited during severe liver injury. CTGF and integrin αvβ6 proteins were highly expressed in DRs of human cirrhotic livers and cholangiocarcinoma. Confocal microscopy analysis of livers from Ctgf promoter‐driven green fluorescent protein reporter mice suggested that oval cells and cholangiocytes were the main sources of CTGF and integrin αvβ6 during liver injury induced by 3, 5‐diethoxycarbonyl‐1, 4‐dihydrocollidine (DDC). Deletion of exon 4 of the Ctgf gene using tamoxifen‐inducible Cre‐loxP system down‐regulated integrin αvβ6 in DDC‐damaged livers of knockout mice. Ctgf deficiency or inhibition of integrin αvβ6, by administrating the neutralizing antibody, 6.3G9 (10 mg/kg body weight), caused low levels of epithelial cell adhesion molecule and cytokeratin 19 gene messenger RNAs. Also, there were smaller oval cell areas, fewer proliferating ductular epithelial cells, and lower cholestasis serum markers within 2 weeks after DDC treatment. Associated fibrosis was attenuated, as indicated by reduced expression of fibrosis‐related genes, smaller areas of alpha‐smooth muscle actin staining, and low collagen production based on hydroxyproline content and Sirius Red staining. Finally, integrin αvβ6 could bind to CTGF mediating oval cell adhesion to CTGF and fibronection substrata and promoting transforming growth factor (TGF)‐β1 activation in vitro. Conclusions: CTGF and integrin αvβ6 regulate oval cell activation and fibrosis, probably through interacting with their common matrix and signal partners, fibronectin and TGF‐β1. CTGF and integrin αvβ6 are potential therapeutic targets to control DRs and fibrosis in related liver disease. (Hepatology 2015;61:678‐691)